2022
DOI: 10.1097/hcr.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Interventions for Patients With Chronic Obstructive Pulmonary Disease

Abstract: Treatment for chronic obstructive pulmonary disease (COPD) ideally would include both pulmonary rehabilitation (PR) and smoking cessation. This article reviews the literature on smoking cessation interventions in those with COPD. Approaches combining behavioral and pharmacological interventions have been most successful for this population and could be integrated into PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
2
1
Order By: Relevance
“…In addition, indirect comparison evidence showed that varenicline was superior to placebo treatment. Our results are supported by several similar reviews reporting on the abstinence effects of NRT, varenicline or bupropion alone or in combination 40–42 . Bupropion did not show a significant smoking cessation effect in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, indirect comparison evidence showed that varenicline was superior to placebo treatment. Our results are supported by several similar reviews reporting on the abstinence effects of NRT, varenicline or bupropion alone or in combination 40–42 . Bupropion did not show a significant smoking cessation effect in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are supported by several similar reviews reporting on the abstinence effects of NRT, varenicline or bupropion alone or in combination. [40][41][42] Bupropion did not show a significant smoking cessation effect in our study. The difference is that Wagena et al reported the smoking cessation efficacy of NRT and bupropion in individuals with COPD in a systematic review in 2004.…”
Section: Discussioncontrasting
confidence: 72%
“…In this issue of the Journal of Cardiopulmonary Rehabilitation and Prevention, Coleman et al report the findings from a prospective, observational, single-site study that examined the relationship between health related quality of life and improvement in physical functioning following participation in an American Association of Cardiovascular and Pulmonary Rehabilitation certified PR program. 2 Nearly, all (96%) patients referred for PR enrolled in their rehabilitation program over more than a decade (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022). Missing data were minimal, with a reported strong completion rate of PR (83% of enrolled patients) and excellent retention rates allowing for analysis (97% of completers), suggesting that the patients included in analyses were not a select subset of those who were referred to or enrolled in PR.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Cardiopulmonary Rehabilitation and Prevention , Coleman et al report the findings from a prospective, observational, single-site study that examined the relationship between health related quality of life and improvement in physical functioning following participation in an American Association of Cardiovascular and Pulmonary Rehabilitation certified PR program 2. Nearly, all (96%) patients referred for PR enrolled in their rehabilitation program over more than a decade (2009-2022).…”
mentioning
confidence: 99%